A review on the pros and cons of online Pharmacies - Jain, V H; Tadv, S A; Pawar, S P (Journal of Applied Pharmaceutical Research, 2017)
Now a day’s buying a medicine online is common practice across the globe, because buyers are used to order for medicines through a click of a button rather than taking a trip to a drug store. Such online websites sell everything from prescription drugs to health related products. Most of such stores are legal outlets that safeguard all traditional procedures related to drug prescription. That is why most buyers are confident about dealing with these stores. But there are quite a few rogue stores that have come up in the recent past over the internet. These stores deal in illegal medications and unapproved drugs, buyers must be aware of such rogue stores. The fact remains that drugs purchased at online drug stores offer high levels of handiness, put forward privacy for the buyer as well as safeguard traditional procedures of prescribing drugs. Thus consumers can use these services with the same confidence as they would have had in the neighbourhood pharmacist. But they must stay away from "rogue sites" that sell unapproved products or sidestep conventional procedures that safeguard the interests of consumers. Additionally, customers have difficulty knowing whether an Internet pharmacy is a legitimate operation.